Neuromuscular training in shod or barefoot conditions equally improved performance in female youth field hockey player: A randomized controlled trial - Schlewing, J.; Jacobs, S.; Hollander, K.; Venter, R. (International Journal of Sports Science & Coaching, 2025)
A growing body of literature addresses the public and scientific interest in barefoot locomotion as an alternative to footwear for running and enhancing physical performance. Little is known about the effects of barefoot training in youth team sport athletes. This randomized controlled trial assessed the efficacy of a nine-week neuromuscular warm-up program (20 minutes twice per week) on balance, functional jumping, speed, acceleration, and agility, in female youth field hockey players. Players (16.2 ± 1.2 years) from three teams from a high school volunteered, consented to participation and were randomly assigned to either a barefoot or shod intervention group. Mixed model ANOVAs were conducted with the full data set of 34 participants as random effects (to account for repeated measurements), and intervention, time, limb side as fixed effects. No statistically significant differences (p > 0.05) were found between the two groups on performance outcomes with small (ES = 0.2) to medium (ES = 0.4) effect sizes. Both groups significantly improved (p < 0.05) their performance pre- to post-intervention in all tests. Performing the warm-up program barefoot or shod appeared to be equally effective to improve physical performance in habitually barefoot youth athletes.